Comparison of three magnetic nanoparticle tracers for sentinel lymph node biopsy in an in vivo porcine model - Pouw, Joost J (Int J Nanomedicine, 2015)
INTRODUCTION: Breast cancer staging with sentinel lymph node biopsy relies on the use of radioisotopes, which limits the availability of the procedure worldwide. The use of a magnetic nanoparticle tracer and a handheld magnetometer provides a radiation-free alternative, which was recently evaluated in two clinical trials. The hydrodynamic particle size of the used magnetic tracer differs substantially from the radioisotope tracer and could therefore benefit from optimization. The aim of this study was to assess the performance of three different-sized magnetic nanoparticle tracers for sentinel lymph node biopsy within an in vivo porcine model. MATERIALS AND METHODS: Sentinel lymph node biopsy was performed within a validated porcine model using three magnetic nanoparticle tracers, approved for use in humans (ferumoxytol, with hydrodynamic diameter d(H) =32 nm; Sienna+(®), d(H) =59 nm; and ferumoxide, d(H) =111 nm), and a handheld magnetometer. Magnetometer counts (transcutaneous and ex vivo), iron quantification (vibrating sample magnetometry), and histopathological assessments were performed on all ex vivo nodes. RESULTS: Transcutaneous “hotspots” were present in 12/12 cases within 30 minutes of injection for the 59 nm tracer, compared to 7/12 for the 32 nm tracer and 8/12 for the 111 nm tracer, at the same time point. Ex vivo magnetometer counts were significantly greater for the 59 nm tracer than for the other tracers. Significantly more nodes per basin were excised for the 32 nm tracer compared to other tracers, indicating poor retention of the 32 nm tracer. Using the 59 nm tracer resulted in a significantly higher iron accumulation compared to the 32 nm tracer. CONCLUSION: The 59 nm tracer demonstrated rapid lymphatic uptake, retention in the first nodes reached, and accumulation in high concentration, making it the most suitable tracer for intraoperative sentinel lymph node localization.